Analisis Pengukuran Efektivitas Peralatan Menggunakan Metode Overall Equipment Effectiveness Analisis Pengukuran Efektivitas Peralatan Menggunakan Metode Overall Equipment Effectiveness - Manaldi, Irsat (Universitas Putra Indonesia YPTK Padang, 2024)
PT. A is an industrial company in the field of four-wheeled vehicle tires that have been bald and then updated or as retreaded tires are called, there are many equipment or machines that are used, in this study focused on one of the machines used by the company, namely building machines or the machine used for the installation of rubber tires with yeast that is still thick. The purpose of measuring the effectiveness of the building machine is because the machine is not working or operating optimally so it is necessary to measure the effectiveness of the building machine in order to determine whether the machine is suitable for use or it is necessary to change the operating system for the use of the building machine. Measuring the effectiveness of building machines using the Overall Equipment Effectiveness (OEE) method using machine working time data, planned downtime data, setup and adjustment data, failure and repair data, product number data, reject and rework products from using building machines, after analyzing the building machines. then the results of OEE are obtained with a value of 42.857% seen from the calculation of the six big losses, the highest losses value is in downtime with a setup and adjustment value of 74.701% and then equipment failure losses of 57.453%. After getting the OEE value, it can be concluded that the OEE value is still below the word class standard.